Power-to-protein: converting renewable electric power and carbon dioxide into single cell protein with a two-stage bioprocess. Issue 12 (21st August 2019) - Molitor, Bastian; Mishra, Akanksha; Angenent, Largus T.
Abstract : To prevent an environmental collapse while feeding a population of 10 billion people, dilute nitrogen in waste streams as a nitrogen source and carbon dioxide as a carbon source should be converted into edible protein as part of the circular economy. Abstract : To prevent an environmental collapse while feeding a future human population of 10 billion people, dilute nitrogen in waste streams as a nitrogen source and carbon dioxide as a carbon source should be recovered and recycled into edible protein as part of the circular economy. For this to work, however, ample renewable electric power would be necessary to provide hydrogen from water electrolysis as an electron donor. We developed a two-stage bioprocessing system as part of a power-to-protein approach to fix carbon dioxide in a first stage by anaerobic acetogenic bacteria, and grow yeasts or fungi in a second stage under aerobic conditions with acetate as the intermediate metabolite. We were able to obtain a carbon yield of 25% as yeast biomass with a protein mass-fraction of ∼40–50% during a proof-of-concept experiment. We developed a technological solution to circumvent conventional agriculture for protein production, while still being able to provide protein for human consumption.